Proceedings of the 2020 International Symposium on Wearable Computers 2020
DOI: 10.1145/3410531.3414303
|View full text |Cite
|
Sign up to set email alerts
|

Face mask design to mitigate facial expression occlusion

Abstract: The COVID-19 pandemic dictated that wearing face masks during public interactions was the new norm across much of the globe. As the masks naturally occlude part of the wearer's face, the part of communication that occurs through facial expressions is lost, and could reduce acceptance of mask wear. To address the issue, we created 2 face mask prototypes, incorporating simple expressive display elements and evaluated them in a user study. Aiming to explore the potential for low-cost solutions, suitable for large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…In this paper, we only test it using wearable physiological signals to maximize the generalizability of it towards different potential application scenarios (e.g., mobile video watching). Facial expressions, for example, are not always possible to capture when users are on the move [ 27 ], wearing a mask [ 121 ] and Head-Mounted Display (HMD) [ 122 ], or under the conditions with inadequate light [ 123 ]. In the future, we will extend CorrNet to use signals in other modalities and investigate whether the recognition accuracy can be further improved.…”
Section: Limitations and Future Workmentioning
confidence: 99%
“…In this paper, we only test it using wearable physiological signals to maximize the generalizability of it towards different potential application scenarios (e.g., mobile video watching). Facial expressions, for example, are not always possible to capture when users are on the move [ 27 ], wearing a mask [ 121 ] and Head-Mounted Display (HMD) [ 122 ], or under the conditions with inadequate light [ 123 ]. In the future, we will extend CorrNet to use signals in other modalities and investigate whether the recognition accuracy can be further improved.…”
Section: Limitations and Future Workmentioning
confidence: 99%
“…In addition, they are assumed to increase mental stress during interpersonal encounters; they might make social judgements more difficult by partially hiding facial features indicating another person's emotions and intentions, thereby hampering smooth social interactions [5][6][7]. Some authors have already suggested how to deal with these social issues, for example by designing face masks with simple expressive display elements [8] or inducing facial muscle paralysis by botulinum toxin targeting the muscles of the top visible half of the face in order to reduce negative emotions and promote well-being for both the mask-wearer and those who come in contact with that individual [9]. However, empirical studies investigating how MNCs influence the recognition of emotions and complex social judgements are sparse [5,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…8 Bottom left: Face masks that mitigate occlusion of facial expressions. 10 Bottom right: Snacap apparatus for snacking detection with smart fabrics. 15 All photos used with permission of the authors.…”
Section: Interactionmentioning
confidence: 99%
“…Genç et al 10 demonstrated how to design face masks with the goal of mitigating the occlusion of facial expression (see Figure 1). This work is of special importance during the ongoing COVID-19 pandemic, where facemasks arguably represent an effective means to limit the spread of the disease and keep people safe.…”
Section: Interactionmentioning
confidence: 99%